Legal Protection Against the Imitation of the Well-Known Jollibee Trademark Based on Court Decision Number 36/Pdt.Sus-Merek/2024/PN.Niaga.Jkt.Pst - Qaterunnada Salshabilla Siregar; Saidin; Zulfi Chairi (Global Journal of Law, AI & Ethics, 2026)
This research aims to analyze the legal framework governing well-known trademarks in Indonesia, the legal consequences of registering trademarks that resemble well-known marks, and the forms of legal protection against the imitation of the well-known trademark Jollibee based on Decision Number 36/Pdt.Sus-Merek/2024/PN Niaga Jakarta Pusat. The research adopts a normative juridical method, employing statutory and conceptual approaches through a literature review of trademark regulations, legal doctrines, and court decisions. The findings indicate that Law Number 20 of 2016 provides protection for well-known trademarks, including those not yet registered, by limiting the application of the first-to-file principle through the requirement of good faith. The a quo decision affirms the application of substantive protection by prioritizing the reputation and distinctiveness of well-known trademarks over mere registration formalities, and by invalidating a trademark proven to imitate and exploit the reputation of the Jollibee trademark. This research concludes that although judicial protection for well-known trademarks in Indonesia has developed in line with international standards, strengthening administrative mechanisms remains necessary to more effectively prevent trademark imitation and to ensure legal certainty